2023
DOI: 10.1007/s11069-023-06259-5
|View full text |Cite
|
Sign up to set email alerts
|

Country-scale assessment of urban areas, population, and households exposed to land subsidence using Sentinel-1 InSAR, and GPS time series

Enrique Antonio Fernández-Torres,
Enrique Cabral-Cano,
Darío Solano-Rojas
et al.

Abstract: The increased need for water resources in urban sprawls and intense droughts has forced more aggressive groundwater extraction resulting in numerous urban areas undergoing land subsidence. In most cases, only some large metropolitan areas have been well-characterized for subsidence. However, there is no existing country-wide assessment of urban areas, population, and households exposed to this process. This research showcases a methodology to systematically evaluate urban localities with land subsidence higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…From the final subsidence results, it is evident that Shenzhen indeed experiences significant land subsidence, with spatial distribution being quite dispersed and the causes The STD of the entire subsidence rate map is 3.9. Reliable subsidence regions were extracted based on ±1.5 times (5.85) the STD, in Figure 6, as within 1.5 times the STD is typically considered stable, while areas beyond this threshold are likely genuine subsidence regions [38,39]. It was observed that significant land subsidence is distributed in the coastal reclamation area on the western side of Bao'an District and in the reservoir area of Qinglinjing.…”
Section: Discussionmentioning
confidence: 99%
“…From the final subsidence results, it is evident that Shenzhen indeed experiences significant land subsidence, with spatial distribution being quite dispersed and the causes The STD of the entire subsidence rate map is 3.9. Reliable subsidence regions were extracted based on ±1.5 times (5.85) the STD, in Figure 6, as within 1.5 times the STD is typically considered stable, while areas beyond this threshold are likely genuine subsidence regions [38,39]. It was observed that significant land subsidence is distributed in the coastal reclamation area on the western side of Bao'an District and in the reservoir area of Qinglinjing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other examples of nationwide A-DInSAR data have been processed to monitor the ground deformations in Greece [22] and Japan [23]. Nationwide and country scale A-DInSAR data are used for several purposes such as strategic water facilities monitoring in Hungary [24], landslide mapping and risk management in Italy [25], railway monitoring in the Netherlands [26], and assessment of areas, population, and households exposed to land subsidence in Mexico [27].…”
Section: Introductionmentioning
confidence: 99%